Conflict of Norms and Ideal Concepts in the Implementation of Restorative Justice in the Criminal Justice System in Indonesia - Achmad Sulchan; Sudarmaji, Aji; Putra, Arlin Aditya Meidiana (KnE Social Sciences, 2025)
The development of the criminal justice system in Indonesia, which was previously implemented with a retributive system, has not been fully able to fulfill the sense of justice for the community. A policy was issued with a restorative justice system that is oriented towards justice, considering that victims of criminal acts can not only experience material losses but are very likely to experience immaterial losses. The definition of restorative justice is an effort to provide a restoration of relationships and redemption of mistakes that the perpetrator of the crime (his family) wants to do to the victim of the crime (his family) with peace efforts outside the court. The intent and purpose are that legal problems that arise as a result of the criminal act can be resolved properly by reaching an agreement between the parties so that there is no element of revenge. This research is a type of normative juridical research, with the specification of descriptive analysis research. It uses research methods obtained by researchers indirectly through intermediary media and using library techniques, in analyzing the formulation of the problem using the theory of law application and the theory of legal protection. Restorative justice is currently not only a concern of the police and the Attorney General’s Office, but also the Supreme Court and several agencies in the Criminal Justice System in Indonesia. This can be seen from the issuance of a Joint Memorandum of Understanding between the Chief Justice of the Supreme Court of the Republic of Indonesia, the Minister of Law and Human Rights of the Republic of Indonesia, the Attorney General of the Republic of Indonesia, the Chief of Police of the Republic of Indonesia Number 131/KMA/SKB/X/2012 Concerning the Implementation of the Application of Adjustments to the Limits of Minor Crimes, the Amount of Fines, Fast Examination Procedures, and the Application of Restorative Justice and Supreme Court Regulation Number 1 of 2024 concerning Guidelines for Trying Criminal Cases Based on Restorative Justice. This requires special attention to the implementation of handling every criminal case that prioritizes restorative justice, because there is a conflict of norms in its application and handling since it is contrary to the Criminal Procedure Code. So, an ideal concept is needed in the criminal justice system in Indonesia, namely its handling by the law enforcement institution of the Attorney General’s Office.